The effect of holistic focus of attention on golf putting in expert - Shin, S.; Kwon, T. (Korean Journal of Sport Science, 2020)
Purpose: The purpose of this study is to investigate the effectiveness of the holistic focus of attention(H-FOA), presented as an alternative attention concept, to explore effective attention focus for the skilled performer.